(untitled) (Global Journal of Management and Business Research, 2022)
This research has been undertaken to explore the idea of agent banking as a mean of financial inclusion to serve the unbanked population expediently. Financial inclusion means bringing the unbanked populace within the formal financial net. This paper is concerned about agent banking initiatives towards financial inclusion as a cheaper alternative. This paper also investigates the significance and competence of agent banking in accessing the lower income people en route for financial inclusion. Based on the secondary sources, this paper reveals the way of opening up new opportunities for banking the unbanked or otherwise. The study concluded that by bringing the channel closer to the client agent banking can give banks more flexibility to distribute financial products and convenient access to formal financial net of a wide range of un-banked and under-banked populace and also reach potential customers which ensure the effective financial inclusion.